Hypersensitivity in Lanthanoids: Symmetry Inversion or Covalency - Pandey, Pravistha; Yadav, A.; Limaye, S.N.; Jayshankar, C.K. (Asian Journal of Chemistry, 2010)
Explanation to the phenomenon of hypersensiqvity has provedto be an intriguing problem. Hypersensitivity may refer to "anenhanced sensitivity of the intensity of specific electronic transitionsto the chemical environment than the normal f-f transitions". Intensityand transition of the hypersensitive peaks are functions of thequantum numbers L and J of the ground state of the lanthanoid ionsand generally, three selection rules: ΔJ≤2, ΔL≤ 2 and somtimesΔS≤O3 have been proposed to regulate the hypersensitive transitions.It was, however, noted that the transitions having a largecontribution from magnetic dipole interactions (ΔJ = 0, ±1) mayalso vary little with a change in environment. Hypersensitivity isthus also called pseudo-quadrupolar transition because it followselectric quadrupole selection rule.